Effect of Interbody Fusion on the Remaining Discs of the Lumbar Spine in Subjects with Disc Degeneration - Ryu, Robert (Orthop Surg, 2016)
OBJECTIVE: To study effects (stress loads) of lumbar fusion on the remaining segments (adjacent or not) of the lumbar spine in the setting of degenerated adjacent discs. METHODS: A lumbar spine finite element model was built and validated. The full model of the lumbar spine was a parametric finite element model of segments L (1–5). Numerous hypothetical combinations of one‐level lumbar spine fusion and one‐level disc degeneration were created. These models were subjected to 10 Nm flexion and extension moments and the stresses on the endplates and consequently on the intervertebral lumbar discs measured. These values were compared to the stresses on healthy lumbar spine discs under the same load and fusion scenarios. RESULTS: Increased stress at endplates was observed only in the settings of L(4–5) fusion and L(3–4) disc degeneration (8% stress elevation at L(2,3) in flexion or extension, and 25% elevation at L(3,4) in flexion only). All other combinations showed less endplate stress than did the control model. For fusion at L(3–4) and degeneration at L(4–5), the stresses in the endplates at the adjacent level inferior to the fused disc decreased for both loading disc height reductions. Stresses in flexion decreased after fusion by 29.5% and 25.8% for degeneration I and II, respectively. Results for extension were similar. For fusion at L(2–3) and degeneration at L(4–5), stresses in the endplates decreased more markedly at the degenerated (30%), than at the fused level (14%) in the presence of 25% disc height reduction and 10 Nm flexion, whereas in extension stresses decreased more at the fused (24.3%) than the degenerated level (5.86%). For fusion at L(3–4) and degeneration at L(2–3), there were no increases in endplate stress in any scenario. For fusion at L(4–5) and degeneration at L(3–4), progression of degeneration from I to II had a significant effect only in flexion. A dramatic increase in stress was noted in the endplates of the degenerated disc (L(3–4)) in flexion for degeneration II. CONCLUSIONS: Stresses are greater in flexion at the endplates of L(3–4) and in flexion and extension at L(2–3) in the presence of L(3–4) disc disease and L(4–5) fusion than in the control group. In all other combinations of fusion and disc disease, endplate stress was less for all levels tested than in the control model.